2020
DOI: 10.3390/mi11100914
|View full text |Cite
|
Sign up to set email alerts
|

An Easy Method for Pressure Measurement in Microchannels Using Trapped Air Compression in a One-End-Sealed Capillary

Abstract: Pressure is one basic parameter involved in microfluidic systems. In this study, we developed an easy capillary-based method for measuring fluid pressure at one or multiple locations in a microchannel. The principal component is a commonly used capillary (inner diameter of 400 μm and 95 mm in length), with one end sealed and calibrated scales on it. By reading the height (h) of an air-liquid interface, the pressure can be measured directly from a table, which is calculated using the ideal gas law. Many factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Pressure decay testing to identify leaks typically requires placing pressure sensors at the inlet and/or outlet of the microchannel ( Casanova-Moreno et al, 2017 ). A reproducible method to characterize microfluidic channel deformations and liquid leaks can be achieved by positioning a sealed capillary tube with a calibrated scale at the channel outlet ( Shen et al, 2020 ). The resolution of the measurement can be improved by simply decreasing the capillary diameter, further resolving the scale, or by complementing the visualization technique with optical detection of the fluid meniscus.…”
Section: Types Of Leakage Testingmentioning
confidence: 99%
“…Pressure decay testing to identify leaks typically requires placing pressure sensors at the inlet and/or outlet of the microchannel ( Casanova-Moreno et al, 2017 ). A reproducible method to characterize microfluidic channel deformations and liquid leaks can be achieved by positioning a sealed capillary tube with a calibrated scale at the channel outlet ( Shen et al, 2020 ). The resolution of the measurement can be improved by simply decreasing the capillary diameter, further resolving the scale, or by complementing the visualization technique with optical detection of the fluid meniscus.…”
Section: Types Of Leakage Testingmentioning
confidence: 99%
“…In this study, the blood and diluent were quantied from a mechanical point of view by using the interface (b) in the coowing channel instead of blood image intensity or air-liquid interface to estimate junction pressure. 16,[50][51][52][53][54][55] Based on the temporal variations of b, the junction pressure of blood was estimated between t 3 and t 4 . In addition, the junction pressure of the diluent was calculated between t 5 and t 6 .…”
Section: Quantication Of Blood Junction Pressure and Pressureinduced...mentioning
confidence: 99%
“…The ranges of values noted here and in the remainder of this section will be used to define the ranges of our targets for the metrics mentioned; despite quoted data for these measurements being sparse in the literature, we found that a common command input for soft actuators is 103.4 kPa [22][23][24][25][26][27][28] while microfluidic output signals vary from 3.4 to 34.5 kPa due to the large resistances of the narrow channels which cause a large pressure drop limiting the output pressure at flow rates relevant to typical soft fluidic actuators. [29] Therefore, a gain range that guarantees that all microfluidic output signal magnitudes can be amplified to drive the largest soft robotic loads is 3-30.…”
Section: Performance Metricsmentioning
confidence: 99%